2021
DOI: 10.1016/j.jamcollsurg.2021.08.686
|View full text |Cite
|
Sign up to set email alerts
|

Primary Surgery with Systemic Therapy in Patients with de Novo Stage IV Breast Cancer: 10-year Follow-up; Protocol MF07-01 Randomized Clinical Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 36 publications
1
65
0
2
Order By: Relevance
“…As with the question regarding the oligometastatic subset, existing data do not specifically address the contribution of primary site local therapy toward achieving long survival. We note that the long-term follow-up results of MF07-01 do suggest a population of long-term survivors 8 ; detailed information on these would be of some interest. It is possible that they consist of patients who entered with minimal metastatic disease, and included some who were assumed to have metastatic disease on the basis of a solitary, unbiopsied bone lesion.…”
mentioning
confidence: 88%
“…As with the question regarding the oligometastatic subset, existing data do not specifically address the contribution of primary site local therapy toward achieving long survival. We note that the long-term follow-up results of MF07-01 do suggest a population of long-term survivors 8 ; detailed information on these would be of some interest. It is possible that they consist of patients who entered with minimal metastatic disease, and included some who were assumed to have metastatic disease on the basis of a solitary, unbiopsied bone lesion.…”
mentioning
confidence: 88%
“…To date, results of four randomized phase 3 trials have been reported [25][26][27][28]. Only in one of these trials, early local therapy of the primary breast tumor improved overall survival in patients with de novo metastatic disease after 10 years of follow-up in a very selected group of patients (i.e., those with HR+/HER2− BC of less than 55 years of age and solitary bone-only metastasis) [28]. Despite better local control, surgery did not improve quality of life [25,27,29].…”
Section: Specific Sites Of Metastasesmentioning
confidence: 99%
“…In a prospective registry study (BOMET MF 14-01), 505 patients with de novo, bone-only MBC demonstrated an improvement in 3-year OS in association with locoregional therapy of the primary tumor (in combination with systemic therapy) compared to systemic therapy alone [30]. Consequently, primary tumor removal in stage IV BC is not recommended with the expectation of survival improvement even in patients with bone-only disease (LoE 1b/B/AGO+/−) [25][26][27][28][29][30]. Only patients with limited or oligometastatic disease and a good response to systemic treatment should be considered for surgical procedures and/or stereotactic treatment of the metastatic sites (LoE 2b/C/AGO+).…”
Section: Specific Sites Of Metastasesmentioning
confidence: 99%
“…Conversely, a number of retrospective (8) studies have suggested that surgical resection is correlated with a survival benefit in pMBC patients (9,10). However, selection bias (11) and other potential confounding factors (12) may have affected these results.…”
Section: Introductionmentioning
confidence: 99%